2017
DOI: 10.1038/sdata.2017.20
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide barcoded transposon screen for cancer drug sensitivity in haploid mouse embryonic stem cells

Abstract: We describe a screen for cellular response to drugs that makes use of haploid embryonic stem cells. We generated ten libraries of mutants with piggyBac gene trap transposon integrations, totalling approximately 100,000 mutant clones. Random barcode sequences were inserted into the transposon vector to allow the number of cells bearing each insertion to be measured by amplifying and sequencing the barcodes. These barcodes were associated with their integration sites by inverse PCR. We exposed these libraries to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…Thus, haploid ESCs enable the isolation of knockout phenotypes in a single round of mutagenesis in a scalable manner. In another application, mutagenized haploid ESCs were screened for drug sensitivity phenotypes [81]. In this study ~100,000 mutant cell clones were generated by a gene trap PB transposon carrying an SA-IRES-neo cassette and a random barcode sequence, whose recovery by next generation sequencing enables quantitation of the number of cells bearing each barcode, and hence each transposon insertion.…”
Section: Transposons and Functional Genomicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, haploid ESCs enable the isolation of knockout phenotypes in a single round of mutagenesis in a scalable manner. In another application, mutagenized haploid ESCs were screened for drug sensitivity phenotypes [81]. In this study ~100,000 mutant cell clones were generated by a gene trap PB transposon carrying an SA-IRES-neo cassette and a random barcode sequence, whose recovery by next generation sequencing enables quantitation of the number of cells bearing each barcode, and hence each transposon insertion.…”
Section: Transposons and Functional Genomicsmentioning
confidence: 99%
“…In this study ~100,000 mutant cell clones were generated by a gene trap PB transposon carrying an SA-IRES-neo cassette and a random barcode sequence, whose recovery by next generation sequencing enables quantitation of the number of cells bearing each barcode, and hence each transposon insertion. These mutant cell pools were then exposed to 13 different drugs followed by an assessment of barcode abundance in order to identify mutations that conferred sensitivity to inhibitors of topoisomerases, PARP and HSP90 [81]. The feasibility of introducing large numbers of mutagenic transposon insertions has also been demonstrated in haploid ESCs established from rats by gene trapping with PB vectors carrying an antibiotic selection marker [82].…”
Section: Transposons and Functional Genomicsmentioning
confidence: 99%
“…Given the cell identity and genomic instability of KBM7 cells, haploid ES cells should have a broader application in genetic screening, such as the one for ‘exit-from-pluripotency’ factors shown here, which obviously cannot be conducted on KBM7 cells. Moreover, targeted mutations or reporter constructs can easily be introduced into haploid ES cells ( 19 , 24 , 26 , 27 ), which should be beneficial for designing more precise genetic screens. For example, via the knock-in of a well-defined lineage-commitment reporter into haploid ES cells before the construction of arrayed mutant libraries, specific differentiation regulators for a particular cell type could be identified.…”
Section: Discussionmentioning
confidence: 99%
“…However, all these screens were performed in mixed pools of a vast number of mutant cells, indicating that the null mutants of interest must be selected either positively using a lethal drug or indirectly using an artificial cellular reporter construct. Recently, a genome-wide barcode transposon screen was used to identify drug-sensitive phenotypes, but the screen was still performed in mixed pools ( 24 ). Thus, the application of haploid ES cells in genetic screening remains limited.…”
Section: Introductionmentioning
confidence: 99%
“…A unidirectional design of the gene-trap cassette overcomes this problem and has facilitated the identification of essential genes in human cells as well as genotype-specific gene requirements by using the distribution of sense and antisense orientations as a readout for gene essentiality ( Wang et al, 2015b ; Blomen et al, 2015 ; Haarhuis et al, 2017 ). Haploid screens have furthermore been employed to study genotypes which sensitize cells to chemical compounds ( Pettitt et al, 2017 ). For instance, we have recently found that loss of the tumor suppressor FBXW7 sensitize cells to Vinca alkaloids.…”
Section: Forward Genetic Screens To Improve Our Understanding Of Drugmentioning
confidence: 99%